Simulation Learning Model Assisted By Audiovisual Media To Improve Learning Outcomes Of Fourth Grade Students At Upt Sd Negeri 066044 Medan Helvetia - Rahmayanti Rahmayanti; Asnita Hasibuan; Matius Eka Wahyudi; Nurlelasari Lubis; Risna Yani Siregar (Journal on Education, 2024)
This research delves into the implementation of instructional improvements over two cycles, wherein the author collects data from these instructional enhancements based on supervisor observations and formative test data across two teaching cycles. The collected data are then consulted with the supervisor as part of performance assessment procedures. In the effort to assist students in enhancing their learning achievements, the author introduces a breakthrough approach by employing a simulation learning model supported by audiovisual media, specifically video and PowerPoint slides (Canva), to provide students with a more vivid and clear presentation of the material. This utilization of simulation learning, aided by audiovisual media, is aimed at helping students overcome boredom and fostering a more enjoyable learning experience through meaningful material observation and direct participation in voice voting simulations.